(untitled) (Latakia University Journal -Basic Sciences Series, 2020)
Phenyl -8- Quinolyl Phosphate (C6H5O)(C9H6NO)(OH)PO was synthesized via reacting Phenol C6H5OH, Phosphorous trichloride POCl3 with 8-hydroxyquinoline C9H6NOH, in order to investigate it to form complex with Cobalt (II), which lead to the Cobalt (II) extraction reaction, afterword the physical constants of the prepared ligand and complex were determined. The structure was confirmed by using FT/IR spectroscopy, UV-VIS spectroscopy, 1H-NMR and 31P-NMR spectroscopy and elemental analysis. The given results have been compared with reference studies.